2014
DOI: 10.1016/j.jcrs.2014.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of cataract phacoemulsification with toric intraocular lenses in addressing astigmatism after keratoplasty

Abstract: Cataract surgery with toric IOL implantation was safe and effective in significantly reducing corneal astigmatism and improving visual acuity in a large cohort of post-keratoplasty eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
3
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 23 publications
6
31
3
4
Order By: Relevance
“…Toric IOLs are used for wider indications; however, evidence-based evaluation of toric IOLs for these purposes is beyond the scope of this review. Positive results have been demonstrated in patients with high degrees of irregular astigmatism after penetrating keratoplasty, 48,49 in patients with pellucid marginal degeneration, 50 and in astigmatic patients undergoing refractive lens exchange. 51,52 Toric IOLs are more expensive than non-toric IOLs, but economic analyses have shown that the lifetime costs are reduced if toric IOLs are implanted in patients with preoperative corneal astigmatism because of the reduced need for postsurgical spectacles.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
“…Toric IOLs are used for wider indications; however, evidence-based evaluation of toric IOLs for these purposes is beyond the scope of this review. Positive results have been demonstrated in patients with high degrees of irregular astigmatism after penetrating keratoplasty, 48,49 in patients with pellucid marginal degeneration, 50 and in astigmatic patients undergoing refractive lens exchange. 51,52 Toric IOLs are more expensive than non-toric IOLs, but economic analyses have shown that the lifetime costs are reduced if toric IOLs are implanted in patients with preoperative corneal astigmatism because of the reduced need for postsurgical spectacles.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
“…Eine Kataraktoperation bei Patienten mit Keratokonus mit oder ohne vorherige pKP kann problematisch sein, weil die Auswahl der Intraokularlinse (IOL) und die Vorhersage des refraktiven Ergebnisses schwierig sind. Bei Patienten, bei denen sowohl ein Astigmatismus nach pKP als auch eine Katarakt vorliegen, haben einige kleine Studien über die Phakoemulsifikation und Implantation einer torischen IOL als alternative Behandlungsmöglichkeit berichtet [8,9,10]. In einem einseitigen Eingriff werden beide Defekte auf einmal korrigiert.…”
Section: Hintergrundunclassified
“…Das in unserem Fall erzielte gute Behandlungsergebnis deckt sich mit dem Bild aus früheren Berichten [8,9,10]. Bisher wurden nur kleine Fallberichte und Fallserien veröffentlicht, die größte mit 22 Augen ist eine retrospektive Fallserie [8].…”
Section: Diskussion Und Schlussfolgerungenunclassified
See 2 more Smart Citations